Interpersonal Processes of Care and Patient Satisfaction: Do Associations Differ by Race, Ethnicity, and Language? - Nápoles, Anna María (Blackwell Science Inc, 2009)
OBJECTIVE: Describe association of patient satisfaction with interpersonal processes of care (IPC) by race/ethnicity. DATA SOURCES/STUDY SETTING: Interview with 1,664 patients (African Americans, English- and Spanish-speaking Latinos, and non-Latino Whites). STUDY DESIGN/METHODS: Cross-sectional study of seven IPC measures (communication, patient-centered decision making, and interpersonal style) and three satisfaction measures (satisfaction with physicians, satisfaction with health care, and willingness to recommend physicians). Regression models explored associations, controlling for patient characteristics. PRINCIPAL FINDINGS: In all groups: patient-centered decision making was positively associated with satisfaction with physicians (B=0.10, p<.0001) and health care (B=0.07, p<.001), and “recommend physicians” (OR=1.23, 95 percent CI 1.06, 1.43); discrimination was negatively associated with satisfaction with physicians (B=0.09, p<.05) and health care (B=0.17, p<.001). Unclear communication was associated with less satisfaction with physicians among Spanish-speaking Latinos. Explaining results was positively associated with all satisfaction outcomes for all groups with one exception (no association with satisfaction with physicians for Latino Spanish-speakers). Compassion/respect was positively associated with all outcomes for all groups with two exceptions (no association with satisfaction with health care among English-speaking Latinos and Whites). CONCLUSIONS: All IPC measures were associated with at least one satisfaction outcome for all groups except for unclear communication.